Technology of thin metal sheet cutting with fiber laser. Issue 1 (February 2021) - Zgripcea, L; Putan, V; Ardelean, M; Birtok Baneasa, C
Abstract: Laser cutting is a thermal cutting process where it is made use of the physical fact that laser light is absorbed in materials. The process is used for many materials in the manufacturing industry. Nowadays, the most suitable laser regarding range of materials, cutting speed, cutting quality is fiber laser. The article studies the correlation between cut quality and process parameters for thin plates, steel and aluminum. The laser machine used for experiments is a Continuous Wawe fiber laser with 1000W power source.